Effects of Multi-Year Maize–Peanut Intercropping and Phosphorus Application on Rhizosphere Soil Properties and Root Morphological and Microbial Community Characteristics - Rentian Ma; Zhiman Zan; Chunli Wang; Shiwei Zhao; Taiji Kou; Nianyuan Jiao (Agronomy)
Intercropping and phosphorus application are effective ways to increase crop yield and improve soil quality. However, the effects of intercropping and phosphorus application on rhizosphere soil properties, root morphology, and microbial characteristics are still unclear. This study focuses on the effects of intercropping and phosphorus fertilizer application (180 kg P2O5 ha−1) on the physicochemical properties, enzyme activity, root morphology, and microbial characteristics of rhizosphere soil in a maize–peanut intercropping field planted for 14 years. The results showed that compared with monoculture, intercropping increased the carbon and nutrient contents. Phosphorus fertilizer application further increased the rhizosphere soil nutrient contents. Compared with monoculture, intercropping increased the urease and saccharase by 14.00 and 7.16% in rhizosphere soil, and phosphorus application increased the urease, alkaline phosphatase, and saccharase in rhizosphere soil by 13.38%, 9.75%, and 24.20% compared with no phosphorus application. Compared with monoculture, intercropping increased the root length, root surface area, root volume, and root tip number by 19.17%, 21.57%, 20.74%, and 28.54%, and phosphorus fertilizer application further increased the root length, root surface area, and root volume by 44.66%, 40.20%, and 41.70%. Compared with monoculture, intercropping increased the Chao index and Shannon index of rhizosphere soil bacteria and fungi by 4.29% and 1.63%, and 27.25% and 7.68%. Intercropping and phosphorus application increased the number of edges and modularity of the network of bacterial and fungal communities. To sum up, the intercropping of maize and peanut improved the nutrient contents and enzyme activity of rhizosphere soil, promoted the growth of the root system, and improved the diversity and connectivity of rhizosphere microbial communities, and the application of phosphate fertilizer further optimized the rhizosphere soil microecological environment. The research results provide a theoretical basis for maintaining the stability and sustainable development of the micro-ecosystem in a maize–peanut intercropping field.